(untitled) (Namibia Educational Reform Forum Journal, 2025)
This study utilized a qualitative methodology and a case study design to investigate the factors contributing to poor performance in English as a Second Language (ESL) among Grade 11 learners in the Oshakati circuit, Oshana region of Namibia. Data were collected through interviews with sixteen participants, including teachers, school principals, Heads of Departments (HODs), learners, and Board members. The study aimed at identifying school environmental factors and home environmental factors that contributed to poor performance in ESL, and to provide recommendations for improving performance in ESL. The findings of the study, derived from thematic analysis, revealed several key themes and sub-themes. Theme identified home environmental factors that affected learners’ performance in ESL in the Oshakati circuit. Sub-themes included lack of parental support, parents’ education level, marital statuses of parents, home language of the learner, and gender roles. Theme 2 identified school environmental factors affecting learners’ performance in ESL, encompassing the following sub-themes: learner attitudes, medium of instruction, school location, peer pressure, lack of resources, and the need to strengthen market information systems. Theme 3 identified strategies to mitigate poor performance in ESL in the Oshakati circuit, including sub-themes such as enhancing language instruction, code switching, parental involvement, individualized support, collaboration and support, and professional development for teachers. These findings provided valuable insights into the factors influencing poor performance in ESL among Grade 11 learners in the Oshakati circuit. The study highlighted the importance of addressing both home and school environmental factors to improve learners’ performance in ESL. The study recommends that educational authorities enhance resources such as language labs and libraries, invest in teacher training for effective ESL instruction, and strengthen parental involvement through workshops to support students at home. Additionally, it suggests adapting the ESL curriculum to be culturally relevant and aligned with students’ experiences while fostering positive student attitudes through initiatives like language clubs and competitions to boost engagement and enthusiasm for learning English.